2017
DOI: 10.1016/j.peptides.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidins display conserved direct antiviral activity towards rhinovirus

Abstract: HighlightsThe host defence peptide LL-37 can reduce Human Rhinovirus 1B (HRV1B) replication in airway epithelial cells.The antiviral activity of LL-37 is sequence specific.LL-37 reduces the metabolic activity of cells infected with HRV1B without inducing substantial apoptotic or necrotic cell death.The antiviral activity of cathelicidin peptides towards HRV1B is conserved in peptides from other mammalian species including pig and sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 52 publications
2
71
0
1
Order By: Relevance
“…The activity of the native LL-37 was significantly greater than scrLL-37, leading us to conclude that LL-37 had a structure-dependent antiviral activity against KSHV. This ability of the native primary structure of LL-37 to inhibit viral infections as opposed to a scrambled version of the peptide has also been observed with a number of other viruses—including DENV (Alagarasu et al, 2017), HAdV19 (Gordon et al, 2005), HCV (Matsumura et al, 2016), HRV (Sousa et al, 2017), HSV-1 (Gordon et al, 2005; Lee et al, 2014), influenza A virus (Barlow et al, 2011; Tripathi et al, 2015a, 2013 White et al, 2017), and RSV (Currie et al, 2013; Harcourt et al, 2016)—suggesting the specific structure, and not simply the charge, of LL-37 is important in its antiviral activity.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The activity of the native LL-37 was significantly greater than scrLL-37, leading us to conclude that LL-37 had a structure-dependent antiviral activity against KSHV. This ability of the native primary structure of LL-37 to inhibit viral infections as opposed to a scrambled version of the peptide has also been observed with a number of other viruses—including DENV (Alagarasu et al, 2017), HAdV19 (Gordon et al, 2005), HCV (Matsumura et al, 2016), HRV (Sousa et al, 2017), HSV-1 (Gordon et al, 2005; Lee et al, 2014), influenza A virus (Barlow et al, 2011; Tripathi et al, 2015a, 2013 White et al, 2017), and RSV (Currie et al, 2013; Harcourt et al, 2016)—suggesting the specific structure, and not simply the charge, of LL-37 is important in its antiviral activity.…”
Section: Discussionmentioning
confidence: 61%
“…The ability of LL-37 to directly inhibit a number of viruses has been reviewed previously (Barlow et al, 2014b), with further activities found against Aichi virus A (Vilas Boas et al, 2017), human adenoviruses 8 and 19 (HAdV-8 and HAdV-19) (Gordon et al, 2005; Uchio et al, 2013), hepatitis C virus (HCV) (Matsumura et al, 2016), human papillomavirus 16 (HPV16) (Buck et al, 2006), human rhinovirus (HRV) (Findlay et al, 2017; Schögler et al, 2016; Sousa et al, 2017), and varicella zoster virus (VZV) (Crack et al, 2012). While LL-37 has only been measured at 0.5 μg/ml in saliva (Bachrach et al, 2006; Takeuchi et al, 2012) and 10 μg/ml in gingival crevicular fluid 29 , the actual physiological concentration may be much higher at sites closer to the oral epithelial cells themselves due to the diffusion of the peptides once released from cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potent antibacterial activity of LL-37 was lost following the addition of carbon black nanoparticles. We recently demonstrated a significant role for cathelicidins in the innate response to influenza virus (45) and rhinovirus 1B (46), and these data suggest that the antiviral activity of LL-37 was also reduced by exposure to nanomaterials. FIGURE 6.…”
Section: Discussionmentioning
confidence: 95%
“…The modulation of viral components necessary for replication and infection (such as HIV reverse transcriptase) has also been described [44]. Moreover, LL-37 showed antiviral activity against non-enveloped virus such as adenovirus, Aichi virus, and rhinovirus [100,115,116]. However, it is suggested that this peptide uses a different mechanism to inhibit non-enveloped viruses such as the adenovirus strains.…”
Section: Avps Derived From Mammalsmentioning
confidence: 99%